Problem of gender equality in the writings of Hassan Al-Turabi: an analytical study on his exegetical views - Solihin, Sohirin Mohammad; Wahyono, Zubaidi (2020)
The paper attempts to expose the views of Abdullah Hasan al-Turabi related to gender equality. It is inevitable that Turabi is one of prominent Muslim scholars in the twentieth century who devoted the whole life in serving the Ummah with the utmost level of capacity. As Muslim thinker he authored dozens of books in different aspects and tafsir al-tawhidi can be considered as masterpiece of his scholarship. Turabi is not only a scholar rather he is a politician who ideas gave tremendous impact and even brought about controversies in the Muslim world. His educational between Islam and Western philosophical thought could be the main factor of coming out into broader spectrum in term of handling the socio-political issues from religious perspectives. Gender equality is one of issues that could be different in his approach toward religious text (Qur’an and Sunnah) compared to other Muslim scholars. The paper aims giving elaboration toward his theoretical framework in exposing the legal concept pertains to concept of leadership (imamah), competency (al-qawamah) and also involvement of Muslim women in socio-political activities.